Utilizing Blockchain Technology to Manage the Dark and Bright Sides of Supply Network Complexity to Enhance Supply Chain Sustainability. (17th June 2022) - Yin, Weili; Ran, Wenxue
Abstract : The supply network becomes more fragile as it becomes more complex, affecting the core firm's performance. While previous research on supply network complexity existence paradox. Therefore, to study the nature of supply network complexity, this paper divides the supply chain complexity utility into positive and negative valences based on the valence framework and divides supply chain complexity into supply base complexity, customer base complexity, and logistics base complexity. Based on the trustworthiness and transparency characteristics of blockchain technology, this paper investigates how to use blockchain technology to reduce the negative valence of supply chain complexity while adapting to or improving the positive valence to improve enterprise competitiveness and supply chain sustainability. As a result, the focus of this paper is on how to better manage supply chain complexity using blockchain technologies to increase supply chain sustainability and viability.